Advancing the Protection of Child Victims of Crime: A Comparative Study of Indonesia and the Philippines - Erly Pangestuti; Dian Arlesti Lukman; Retno Sari Dewi; Jessica Mae S. Monzon (Jurnal Dinamika Hukum, 2026)
The protection of children as victims of crime remains one of the major challenges in modern child protection legal framework systems, particularly in developing states such as Indonesia and the Philippines. Although both states have constitutional commitments and national policies aimed at safeguarding children’s rights, the implementation of protection for child victims often encounters structural, cultural, and institutional obstacles. This article examines the role of child protection legal framework in strengthening the protection of child victims through a comparative analysis of legal frameworks, policies, and law enforcement practices in both states. The study employs a comparative legal research method by analyzing relevant legislation, jurisprudence, and public policies on child protection. The findings indicate that Indonesia and the Philippines both possess a strong legal foundation for child protection, as reflected in the Child Protection Law of 2002 (amendment 2014 and 2016) and the Philippines’ Republic Act No. 7610 of 1992. However, the effectiveness of implementation remains limited due to inadequate inter-agency coordination, resource constraints, and a lack of sensitivity among law enforcement officials toward child victims. This study underscores that child protection legal framework plays a crucial role not only as a normative regulatory instrument but also as a means of social engineering that promotes justice and the well-being of child victims of crime. The main recommendations include strengthening institutional capacity, enhancing training for law enforcement personnel, and harmonizing cross-sectoral policies to achieve more effective and sustainable child protection.